Detection of mecA Genes from Staphylococcus aureus Bacteria in Raw Cow Milk in the Surabaya Regional Farm - Putri Lestari, Ajeng Anindhita; Prayekti, Endah Prayekti; Hidayat, Muhammad Taufiq (Poltekkes Kemenkes Mataram, 2024)
Milk is a very important food ingredient in meeting nutritional needs and a good growth medium for microorganisms. Staphylococcus aureus bacteria are pathogens that often contaminate milk. Staphylococcus aureus bacteria can cause a disease called mastitis. The acropolis is very susceptible to infections, treatment and prevention need to be done to avoid mastitis. Treatment of mastitis until now still uses antibiotics, improper use of antibiotics can cause Staphylococcus aureus resistance to antibiotics. The mecA gene is the gene responsible for beta-lactam antibiotic resistance. This study aims to determine the presence of the mecA gene in Staphylococcus aureus isolate from raw cow's milk. The samples from this study are 24 samples taken from dairy farms in the Surabaya Region. Isolation of Staphylococcus aureus bacteria by conventional microbiology based on culture properties, Gram staining and biochemical tests. The results of this study showed that there were 5 samples that were positive for Staphylococcus aureus. Molecular detection by PCR of the mecA gene in Staphylococcus aureus was not found in the five Staphylococcus aureus isolates. Based on this study has the result that the sample found Staphylococcus aureus but no mecA gene was found.